Potencial utilization of skipjack tuna (Katsuwonus pelamis) in Bone Bay - Umar, Moh. Tauhid; Safruddin, Safruddin; Zainuddin, Mukti (Hasanuddin University, 2019)
The skipjack tuna (Katsuwonus pelamis) resource in Bone bay has long been exploited, but information about the sustainable potential of this fish resource in Bone bay waters is still very limited. The aim of this research is to estimate potential of fish resources that include catch per unit effort (CPUE ), the maximum sustainable yield (MSY), optimum effort, exploitation rate and total allowable catch (TAC) of skipjack tuna in the waters of Bone bay. This study uses time series data, namely annual data from the fisheries statistics report at Marine and Fisheries Service, South Sulawesi Province from 2006-2015. The method used to estimate the potential of fish resources in this study is the surplus production method with the Schaefer model. The results showed that the average production and standard efforts in the 10-year period were 14689.7 tons and 914 standard units respectively. The estimation results obtained MSY and optimum effort per year are 22561.4 tons and 1730 standard units, and allowed catches (TAC) of 18049.2 tons per year. The level of exploitation of skipjack tuna resources in the waters of Bone Bay does not over exploited every year except in 2017.Keywords: potential of fish resources, skipjack tuna (Katsuwonus pelamis), MSY, TAC, Bone bay